Scenarios for collaborative architectures for monetizing broadcast archive clips - Bachmayer, S.; Lugmayr, Artur; Kotsis, G. (2011)
Broadcasters own huge assets in form of audio-visual archives or licensing rights for content from 3 rd parties. A few public broadcasters grant free access to their consumer of their own produced content. Another trend is social media networks, where consumers are exchanging selected clips as form of digital goods on the Internet. Within the scope of this paper we especially focus on the investigation of this scenario, and research the business opportunities as well as the underlying potential digital platform for exchanging that can be utilized for exchanging digital clips and monetizing these as digital goods. However, the main focus will be on the presentation of the scenarios and the architecture to support the exchange of digital goods in a social media setting. © 2011 ACM.